Case Report: Pulmonary echinococcosis misdiagnosed as bronchogenic pulmonary cysts - Qingcheng Yang; Lyubo Wang; Yuanlong Shi; Siyun Liu; Daoguang Fan; Bencheng Wu; Yi Duan; Chenjun Xin; Lincan Duan (Frontiers in Medicine)
Echinococcosis, also known as hydatid disease, is a zoonotic parasitic infection that poses a significant risk to human health. This article delineates the diagnostic and therapeutic course of a patient afflicted with pulmonary echinococcosis who was admitted to the Department of Thoracic Surgery II at Yunnan Cancer Hospital in April 2024. The patient exhibited a history of extensive exposure to livestock and a penchant for consuming undercooked meat. Prior to undergoing surgical intervention, the patient was initially diagnosed with bronchogenic pulmonary cyst. However, subsequent pathological examination revealed a diagnosis of pulmonary echinococcosis. The rarity of the disease and the paucity of experience in diagnosis and treatment rendered the patient’s case a valuable opportunity to elucidate the diagnostic and therapeutic journey. This report aims to provide a comprehensive reference for the accurate identification and treatment of pulmonary echinococcosis in future clinical practice.